A new fluorogenic probe for the selective detection of carbon monoxide in aqueous medium based on Pd(0) mediated reaction. Issue 21 (13th February 2015) - Pal, Siddhartha; Mukherjee, Manjira; Sen, Buddhadeb; Mandal, Sushil Kumar; Lohar, Somenath; Chattopadhyay, Pabitra; Dhara, Koushik
Abstract : A coumarin-based fluorogenic probe, PCO-1, detects carbon monoxide selectively in buffer at pH 8.0 through the intramolecular cyclization–elimination pathway based on Pd(0) mediated reaction. Abstract : A coumarin-based fluorogenic probe, PCO-1, senses carbon monoxide (CO) selectively in HEPES buffer at pH 8.0 through the intramolecular cyclization–elimination pathway based on Pd(0) mediated reaction. The probe exhibits a 'turn-on' response of CO over a variety of relevant reactive oxygen, nitrogen and sulfur species.